Active Commuting to School, Physical Activity, and Behavior Problems Among Third‐Grade Children. (10th September 2018) - Mann, Mana; Silver, Ellen J.; Stein, Ruth E. K.
ABSTRACT: BACKGROUND: We examined factors associated with active commuting to school and the relationships of active commuting and physical activity to child‐ and teacher‐reported internalizing and externalizing behavior problems in a sample of third graders. METHODS: The study sample consisted of 13, 166 third graders enrolled in the Early Childhood Longitudinal Study Kindergarten Class of 1998‐1999. "Active" commuters were children who walked to school and "passive" commuters were those who took the bus or were driven. Linear analyses evaluated differences in behavior problems by school commute, physical activity, and sports team participation after adjusting for sociodemographic, regional, and neighborhood factors. RESULTS: Overall, 11% of children actively commuted. Type of commute differed by sociodemographics, region, urbanicity, school type, and neighborhood safety. Active commuters had less general physical activity participation and sports team participation. Commuting type and general physical activity were not associated with behavior problems, but sports team participation was associated with fewer child‐reported internalizing and externalizing behaviors as well as fewer teacher‐reported internalizing behaviors. CONCLUSIONS: Our findings demonstrate the ongoing need for creating and maintaining physical activity programs (such as sports teams) among school‐aged children to optimize children's overall health and well‐being.